Strengthening Creative Thinking Ability: A Project-Based Physics Assessment Instrument - Viyanti; D. Herliani; Rosidin, Undang (Pendidikan Fisika FITK UIN Sunan Kalijaga, 2022)
Creative thinking is one of the skills needed in education in the 21st century which requires students to think appropriately in accordance with relevant and diverse sources of information. This study examines students' creative thinking skills during project-based physics learning In the subject of work and energy. The study was conducted by 36 students in their first year of high school. It was obtained using a simple random sampling technique in one of the high schools in Kotaagung, Tanggamus. The assessment tool utilized in the study was a project assessment tool supported by a worksheet on business and energy materials. It was a valid, reliable, and useful instrument. According to the research's findings, 36 students achieved the following levels of creativity in each indicator: 1) fluency (69%); 2) flexibility (80%); 3) originality (69%); and 4) elaboration (68%).